PLANETARIUM DESIGN BANDUNG ASTRONOMICAL GALLERY - June Ekawati (Sean Institute, 2022)
The development of technology and science today can provide many benefits as well as convenience and comfort in today's life. Changes every year are always made in order to produce better ones with more efficiency, effectiveness, and accuracy in their use. One of the fields of science that is experiencing rapid development at this time is the field of astronomy. But with the lack of well-known science of astronomy, there is a gap in the understanding of astronomy with other sciences. To popularize this knowledge, means must be made that can support activities about astronomy and provide information related to astronomy. And the creation of educational facilities such as planetarium galleries, it is hoped that astronomy can be better known for the existence of this container. The city of Bandung itself is the center of astronomy in Indonesia because of the observatory in Lembang Bosscha, information about astronomy from outside Indonesia enters through the city of Bandung because of the EXISTENCE of the UPT Observatory Bosscha. Bandung has the potential to develop for a place of astronomical development not only in terms of information and can become one of the education education because Bandung not only has supporting personnel but the city of Bandung as a student city, cultural center and main recreational destination in West Java has the potential to become a place for recreation and also education for the community